Incorporating Non-rigid Registration into Expectation Maximization Algorithm to Segment MR Images - Pohl, Kilian M; Wells, William M; Guimond, Alexandre; Kasai, Kiyoto; Shenton, Martha E; Kikinis, Ron; Grimson, W Eric L; Warfield, Simon K (Medical image computing and computer-assisted intervention : MICCAI ... International Conference on Medical Image Computing and Computer-Assisted Intervention, 2002)
The paper introduces an algorithm which allows the automatic segmentation of multi channel magnetic resonance images. We extended the Expectation Maximization-Mean Field Approximation Segmenter, to include Local Prior Probability Maps. Thereby our algorithm estimates the bias field in the image while simultaneously assigning voxels to different tissue classes under prior probability maps. The probability maps were aligned to the subject using nonrigid registration. This allowed the parcellation of cortical sub-structures including the superior temporal gyrus. To our knowledge this is the first description of an algorithm capable of automatic cortical parcellation incorporating strong noise reduction and image intensity correction.